The Incorporation of Emotional Intelligence Education in English Textbooks for 12th Grade High School Students: A Content Analysis - Go, Priskila; Nurkhamidah, Neni (PRIMACY Journal of English Education and Literacy, 2024)
In recent years, due to the rapid development of artificial intelligence (AI), emotional intelligence (EI) has become increasingly valuable as its uniquely human qualities cannot be replicated by machines (Beck & Libert, 2017). As an impact of this phenomenon, EI has also become a topic that is acknowledged as important in the educational landscape, including Indonesia’s. This is mandated by the current Indonesian curriculum, namely Kurikulum Merdeka (Merdeka Belajar Curriculum). The purpose of this study is to discuss the ways in which EI skills are taught in the English textbook used by 12th graders in Indonesian public high schools. This study adapted the content analysis method used by Babaei & Abdi (2014), which used Goleman's Emotional Intelligence Checklist to observe the emotional intelligence components in the dialogues, reading texts, and exercises in the textbook. The result of the study shows that 46.6% of the examined dialogues, 78.6% of the examined reading texts, and 40.9% of the examined exercise elements contain various EI components, including those required by the curriculum regulations. They are included in the content in the form of character dialogue and description, advice, questions or discussion and project activities.